A coupled method of on-line solid phase extraction with the UHPLC‒MS/MS for detection of sulfonamides antibiotics residues in aquaculture. (September 2020) - Li, Tao; Wang, Ce; Xu, Zhaoan; Chakraborty, Amit
Abstract: The use of a variety of antibiotics in fish farming raises serious concern about the development of antibiotic resistance. Sulfonamides antibiotics (SAs), which are widely used in aquaculture and generate large eco‒toxicological effects with significant mutagenicity and teratogenic consequences, are still difficult to determine in aquatic organisms. In this study, an automatic technology was developed by coupling on‒line solid phase extraction system (on‒line SPE) with ultra‒high‒performance liquid chromatography spectrometry‒mass spectrometry (UHPLC‒MS/MS). Particularly, using a single on‒line column in the process of sample pretreatment, e.g., HLB or C18, phospholipids that potentially caused the matrix effect cannot be removed form biological sample. We applied a mixed cation exchange column (Oasis® MCX) connected with a hydrophilic lipophilic balance column (Oasis® HLB) in series in on‒line SPE clean‒up to remove interferences and finally obtained a clear and stable eluant. The on‒line SPE working conditions and UHPLC‒MS/MS parameters were optimized for their sensitivity, accuracy, decision limit, and detection capability, which were further calibrated for fish, shrimp and crab. The results showed that the limits of detection and limits of quantification ranged from 1.46 to 15.5 ng/kg, and 4.90–51.6 ng/kg, respectively. Accuracy values covered 71.5%–102% at the three concentration levels (0.1, 0.5, 1.0 μg/kg) for all compounds and average repeatability (relative standard deviation, RSD%) ranged from 3.47% to 14.2%. This on‒line SPE coupled with UHPLC‒MS/MS method is a way forward for an automatic, powerful detection technology for determination of antibiotics from complex matrix. Highlights: A method for determination of sulfonamides in aquatic organisms was developed. The quantitative method was based on on-line SPE-UHPLC-MS/MS technology. On-line SPE clean-up consisted of two SPE columns connected in series. Method validation was according to the European Union Decision 2002/657/EC. Antibiotics concentrations were determined in fish, shrimp and crab.